Inward rectifying Kir4.1 channels regulate oligodendrocyte precursor cell differentiation and CNS myelination in vivo. (11th June 2023) - Liu, Jia-Yu; Zhou, Liang; Shen, Ying
Highlights: Kir 4.1 deletion in OLs leads to myelin deficits. Kir 4.1 is required for adult myelin maintenance. Kir 4.1 affects OPC differentiation in the developing brain. Abstract: The functions of Kir 4.1 in oligodendrocyte development have been in controversial. We recently reported that inhibiting Kir 4.1 impeded oligodendrocyte precursor cell (OPC) differentiation and oligodendrocyte (OL) maturation, due to Kir 4.1 altering intracellular pH of OPCs through Na + /H + exchangers. However, our conclusion was limited by in vitro observation, thereby it becomes necessary to seek in vivo evidence to determine the roles of Kir 4.1 on OPC development and CNS myelination. Here, we used Olig1 -Cre to knockout Kir 4.1 in OPCs from the early developmental stage. We found that the cell-specific deletion of Kir 4.1 significantly impeded OPC differentiation and reduced the number of mature OLs in the cerebral cortex and the corpus callosum. Hence, our in vivo evidence supports that Kir 4.1 can regulate OPC differentiation and is essential to CNS myelination.